KESADARAN PRODUK RAMAH LINGKUNGAN SEBAGAI MEDIASI: KEPEDULIAN LINGKUNGAN DAN EFEKTIVITAS SOSIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN - Farhanah, Arina; Kusumastuti, Aprillia Elly (ECONBANK: Journal of Economics and Banking, 2020)
Issues are spread about environmental conditions to develop and many become the topic of discussion. One prevention that can be done is to use green products. this study aims to explain environmental concern and social media influence on purchase decisions by mediating green product awareness. The population in this study is the people of Semarang City. The number of samples used was 100 respondents who had bought Lock & Lock products at least once. The sampling technique used is nonprobability sampling with a purposive sampling method. Data were collected using a questionnaire. The analysis technique used is the path analyst and Sobel test. The results of the analysis show that environmental concern and social media cannot directly influence purchasing decisions, but rather must be mediated through green product